Multiple Myxomas in Right Ventricle A Case Report of Carneys Syndrome - Fatema, Nilufar; Ahmed, Sheikh Foyez; Azad, Nazim Al; Jannat, Maftahul; Haque, Md Azizul; Islam, Md Tauhidul; Siddique, Md Abu; Banerjee, Sajal Krishna; Rahman, AKM Fazlur; Ahsan, Syed Ali; Ahmed, Choudhury Meshkat; Shafiuddin, Md; et al. (University Heart Journal, 2014)
No Abstract DOI: http://dx.doi.org/10.3329/uhj.v9i1.19515 University Heart Journal Vol. 9, No. 1, January 2013; 56-58